Hubungan Persepsi dan Sikap Civitas Akademika terhadap Kesesuaian Peraturan Perundangan dengan Pancasila - Silverius Yoseph Soeharso; Aisyah (Jurnal Ilmiah Psikologi MIND SET, 2021)
Pancasila is the source of all sources of law in Indonesia, therefore all legal arrangements must originate from Pancasila. However, in reality there were hundreds of laws that were canceled because they were not in accordance with Pancasila. The purpose of this research is to examine the description of the perceptions and attitudes of the academic community towards the conformity of laws and regulations with Pancasila. Respondents in this study are the academic community. The method used in this research is correlation analysis. The measurement used in this study was made by the research team based on Sarwono's theory of perception (2009) and Oskamp & Schultz's theory of attitudes (2005). This study found that there is a significant positive relationship between perception and attitude of the academic community towards the conformity of the Indonesian law with Pancasila. It can be concluded that the academic community in general understands that there is a mismatch between the Inodnesian Law and Pancasila.